2015
DOI: 10.1007/s12035-015-9545-z
|View full text |Cite
|
Sign up to set email alerts
|

nNOS Translocates into the Nucleus and Interacts with Sox2 to Protect Neurons Against Early Excitotoxicity via Promotion of Shh Transcription

Abstract: Cerebral ischemic stroke is a major public health problem leading to high mortality rates and disability in adults. The NMDA receptor (NMDAR)/neuronal nitric oxide synthase (nNOS)/NO-dependent excitotoxicity has been recognized to play an important role in cerebral ischemic stroke pathogenesis. Accumulating evidence suggests that the biological function of nNOS is associated with its ability to couple proteins and its subcellular localization. Previously, we and others determined that nNOS could translocate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…), but is also ascribed a neuroprotective role in the early defence against excitotoxicity (Zhang et al . ). nNOS has not previously been studied in the periphery in regard to cerebral ischaemia, but dual roles of NO release in the ENS have been described (Sandgren et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…), but is also ascribed a neuroprotective role in the early defence against excitotoxicity (Zhang et al . ). nNOS has not previously been studied in the periphery in regard to cerebral ischaemia, but dual roles of NO release in the ENS have been described (Sandgren et al .…”
Section: Discussionmentioning
confidence: 97%
“…The expression of nNOS gradually increases in the central nervous system after an ischaemic insult (Farkas et al 2007;Chen et al 2014;Zhang et al 2016). However, the functional consequences of this are not fully understood.…”
Section: Nnos Expression Was Unaffected After Cerebral Ischaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…However Sox2-deleted NSCs demonstrate low expression of Shh in vitro (Han et al, 2008; Favaro et al, 2009). Recently, Zhang et al demonstrated that a nNOS-Sox2 complex promoted the transcription of Shh in neurons following glutamate stimulation (Zhang et al, 2016). As shh/Gli has an important role in NSCs, we measured the expression of Shh, which showed an analogous spatio-temporal change in parallel with Sox2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as a nuclear transcription factor, Sox2 can regulate the transcription of downstream genes. Early research showed that sonic hedgehog (Shh) is a direct target gene of Sox2 (Zhang et al, 2016). Furthermore, it is a powerful regulator of adult hippocampus neurogenesis and is essential for the maintenance of adult stem cell properties (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%